The Violence Based on Religion as a Factor of the Distribution of the World Political Process - Mykhalskyi, Ihor (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The article deals with the role of political violence in the modern world through the prism of exacerbation of cultural-religious contradictions. Based on the analysis of statistical data, the tendencies of the spread of confrontation on religious grounds have been revealed, such as discrimination and impairment of the rights of religious communities, ethnic-confessional conflicts, and the spread of transnational religious terrorism. It is concluded that the politicization of religions is a significant factor of social and political destabilization both at the regional and global levels